Lessons from comedy group management in Yogyakarta: a case study of organizational management practices of â€œDouble Sâ€ group as a microenterprise - Putra, Trisna Pradita; Irawanto, Budi; Haryono, Timbul (ASSOCIATION FOR SCIENTIFIC COMPUTING ELECTRICAL AND ENGINEERING (ASCEE), 2024)
Performing arts organizations at the micro level often face challenges threatening their sustainability. The big challenge is how good organizational management practices can be done with limited resources, local competition, and changing market dynamics. This research aims to examine and improve the effectiveness of micro-organizational management in the context of performing arts, focusing on a case study of the comedy group â€œDouble Sâ€ in Yogyakarta. This research is exploratory, using a qualitative approach and case studies as an analytical framework. Data were collected through in-depth interviews with group members, direct observation of performances, and document analysis related to organizational management. Organizational management concepts, such as strategic planning, organizing, and leadership, were applied in the context of micro-performing arts. The results showed that comedy groups as micro organizations have unique characteristics of organizational management practices, namely, organizational management in the context of a very flexible comedy group and the emergence of the central role of the artist who doubles as the group manager. Although it is done with complete improvisation and tends to be unstructured, the flexibility of organizational management has become a strength for the comedy group. The flexibility of management allows the comedy group to adapt to various uncertainties. Microorganizations need managers who have improvisational skills in organizational management. This research contributes to understanding organizational management at the micro level in the performing arts industry. The practical implication is to guide similar performing arts groups to improve competitiveness and sustainability. This study can also serve as a reference for further research on micro-level performing arts organization management and its influence on the development of local performing arts.